1981
DOI: 10.1177/019459988108900129
|View full text |Cite
|
Sign up to set email alerts
|

The Implication of Viruses in Idiopathic Sudden Hearing Loss: Primary Infection or Reactivation of Latent Viruses?

Abstract: Seventy-seven paired serum samples from patients with known idiopathic sudden hearing loss (ISHL) were surveyed using viral serologic methods. Fifteen different viruses and Mycoplasma pneumonia were the agents tested. We determined an incidence of 65% (49/77) of documented significant seroconversions to one or more of the agents surveyed. Multiple agents were involved in 24 of the 49 positive cases we studied. Influenza virus Group B in 14 (18%) and rubeola in 12 (16%) were the most prevalent, followed by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
3

Year Published

1987
1987
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(44 citation statements)
references
References 12 publications
1
38
0
3
Order By: Relevance
“…We demonstrated that there is an association between VZV, CVB5 and influenza B and inner ear diseases, especially among patients with SSHL, in line with some previous works. Our results are in line with Veltri et al [77] , who investigated 77 patients with SSHL and seroconversion reactions [77] . After testing 15 different viruses, they observed an incidence of 65% for significant seroconversions to one or more of them.…”
Section: Comments On the Resultssupporting
confidence: 93%
“…We demonstrated that there is an association between VZV, CVB5 and influenza B and inner ear diseases, especially among patients with SSHL, in line with some previous works. Our results are in line with Veltri et al [77] , who investigated 77 patients with SSHL and seroconversion reactions [77] . After testing 15 different viruses, they observed an incidence of 65% for significant seroconversions to one or more of them.…”
Section: Comments On the Resultssupporting
confidence: 93%
“…However, viral etiology has been a popular causative theory in recent years. The proposed viral hypothesis includes direct viral invasion of the fluid and soft tissues of the cochlea (cochleitis) or SGNs (neuritis), reactivation of a latent virus within a spiral ganglion, and an indirect immune-mediated mechanism [6,7]. Viral etiology of ISSHL has received a variety of support from temporal bone analysis and clinical characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…A few kinds of viruses, such as mumps, measles, and rubella, have been shown to be associated with ISSHL by sensitive serological techniques, such as polymerase chain reaction (PCR) and immunoglobulin titers [7,8,9]. However, the decline of the incidence of these virus infections due to worldwide immunization against them has not decreased the incidence of ISSHL [10].…”
Section: Introductionmentioning
confidence: 99%
“…Wilson [2] hatte bei 7,4% (n = 122) eine Serokonversion für anti-HSV-1-Antikörper und bei 5,0% der Patienten für anti-VZV-Antikörper nachgewiesen. Damit korrespondierend fanden auch Veltri et al [22] bei 8% (n = 77) einen Anstieg von anti-HSV-Antikörpern.…”
Section: Diskussionunclassified